(untitled) (Research, Society and Development, 2020)
The researchobjector analyze the main developments undertaken in the referencial curricular of Rondônia, about the remaining communitiess of quilombolas. To reach the goal, a literature review was conducted, directed at authors such as: Acosta-Leyva, Farias Jr, Fotopoulos, Teixeira, among others. After the bibliographic studies, it was inferred -se quethat, school education in quilombola communities, raises differently from formal public education, this due to the question “temporal space”, in which each community has its own education, culminating with cultural aspects, peculiar knowledge, life experiences, traditions, customs, beliefs and, the relationship in which they maintain with nature. Therefore, the cultural diversity of these communities are forms of learning, that is, it qualifies their space (territory and territoriality) as being, an educational environment, in the perspective of strengthening the cultural indenitary memory.